159k views
1 vote
What is 2×4÷6 (8×3)-6=Y

User Nachodd
by
5.9k points

2 Answers

3 votes

To solve this problem, you need to do it in this order: PEMDAS

(Parentheses, Exponent, Multiplication, Division, Addition, Subtraction)


2 × 4 ÷ 6(8 × 3) - 6 = Y First simplify inside the ( ), and multiply 8 by 3

2 × 4 ÷ 6(24) - 6 = Y Now multiply 6 and 24

2 × 4 ÷ 144 - 6 = Y Multiply 2 and 4

8 ÷ 144 - 6 = Y Divide 8 and 144

18 - 6 = Y Subtract 18 and 6

12 = Y

User Csavvy
by
6.1k points
4 votes

Hey there!

2 × 4 ÷ 6 (8 × 3) - 6 = y

y = 8 ÷ 6(24) - 6

y = 4 ÷ 3(24) - 6

y = 32 - 6

y = 26


Therefore, your answer is: y = 26


Good luck on your assignment & enjoy your day!


~Amphitrite1040:)

User Timber
by
6.0k points